Fully customized placement of orthodontic miniplates: a novel clinical technique - Hourfar, Jan; Kanavakis, Georgios; Goellner, Peter; Ludwig, Björn (Head & face medicine, 2014)
The initial stability and survival rate of orthodontic mini-implants are highly dependent on the amount of cortical bone at their insertion site. In areas with limited bone availability, mini-plates are preferred to provide effective skeletal anchorage. The purpose of this paper was to present a new clinical technique for the insertion of mini-plates.
Gesehen am 25.08.2020